THE NEEDS TO ENHANCE ORAL COMMUNICATION TECHNIQUES FOR FINE ARTS STUDENTS TO PRESENT ARTWORKS - Chuenchaikit, Tidarat (Thai Interdisciplinary and Sustainability Review, 2023)
As the Thai government has a policy to support the creation of Soft Power to raise the level and develop the knowledge, abilities, and creativity of Thai people to create product value and generate income, as well as further develop art, culture, and promote local wisdom. The purpose of the study was to assess and prioritize the needs of communication techniques in oral presentation for fine arts students. The data was collected from 140 undergraduate students majoring in fine arts, King Mongkut’s Institute of Technology Ladkrabang. The research instrument was a need assessment questionnaire of actual and expected situation about oral techniques for art presentation consisting of 6 techniques as follows: 1) techniques for structuring speech content 2) persuasive speaking techniques 3) audience analysis techniques 4) tone of voice techniques 5) story preparation techniques and 6) body language techniques. The result of Priority Needs Index Modified was as follows: 1) The actual situation assessment was at a moderate level. The expected situation assessment result was high. 2) The result of the Priority Needs Index Modified analysis can be arranged as follows: persuasive speaking techniques, techniques for structuring speech content, tone of voice techniques, audience analysis techniques, body language techniques, story preparation techniques